Cashew apple juice as substrate for microbial fuel cell. (15th June 2019) - Divya Priya, A.; Pydi Setty, Y.
Highlights: Cashew apple juice can be used as a potential substrate for MFC. Dual chambered acrylic MFC with MEA was used. Maximum power and current density and OCV were reported. Abstract: Cashew apple juice which is an agro-based residue, more than 90% of the cashew apple is left as waste in the land after removing the cashew nuts. As a low cost agricultural waste, it is a potential source of substrate for industrial and biotechnological processes. It is reported that Cashew apple juice is used as a potential source of substrate for the production of bio ethanol, and other value added products such as dextran, lactic acid, mannitol and oligosaccharides etc. through fermentation. In this work, we report that the clarified cashew apple juice can be used as a potential substrate for microbial fuel cell generating open circuit voltage of 0.4 V and maximum power density and current density of 31.58 mW/m 2, 350 mA/m 2 respectively.